A comparative study of open (Milligan-Morgan) versus closed (Ferguson) haemorrhoidectomy with and without internal sphincterotomy - Singh, Rita; Reddy, T. Rudra Prasad; Kumar, T. Santosh (International Surgery Journal, 2019)
Background: Normal anal canal contains cushion of submucosa with vascular tissues. When cushions become abnormal , cause symptoms. This clinical condition is known as haemorrhoids. Haemorrhoidectomy is surgery for haemorrhoids, which can be performed by Milligan-Morgan (open technique) or Ferguson (close technique) methods. This study is conducted to compare different surgical modalities of treatment for haemorrhoids. Methods: In total, 232 patients suffering from haemorrhoids with or without fissures were included in the study. Patients were categorized into two groups. Patients undergoing open technique were designated as open group, similarly patients undergoing close technique were designated as close group. In both groups for few patients internal sphincterotomy (I.S.) was performed. Post-operative pain was assessed by visual analogue scale in all groups, per operative haemorrhage was assessed by number of swabs used during surgery and VAS estimation, operating time and post-operative hospital stay were recorded. Results: 136 patients were suffering from haemorrhoids with fissures. Of these 84 patients were operated by open technique and 52 patients by close technique. In all 136 patients, internal sphincterotomy was performed. Remaining 96 patients were suffering from only haemorrhoids. Of these 30 patients were treated by open technique with I.S., 30 patients were treated by close technique only. 25 patients were treated by close technique with I.S. and 10 patients were treated by close technique without I.S. Close group and open group with I.S. experienced less pain compared to without I.S. in both groups. Per operative haemorrhage and hospital stay in close group was less . Operative time in open group was less compared to close group. Conclusions: Ferguson procedure is found to cause less post-operative discomfort. Addition of internal sphincterotomy is having a positive effect in reducing post-operative pain.